Adlay seed hull polysaccharide as a green corrosion inhibitor for mild steel in acid solution: surface analyses and theoretical calculations. (2nd November 2021) - Chen, Cai-Yang; Yu, Chong; Li, Hui-Jing; Zhang, Chi; Zhang, Weiwei; Wu, Yan-Chao
Abstract : Adlay seed hull polysaccharide was developed here as a green corrosion inhibitor for mild steel in 1 M HCl solution, and its inhibition effect was studied with electrochemical experiments, theoretical calculations, etc. Abstract : Adlay seed hull polysaccharide (ASP) was developed here as a green corrosion inhibitor for mild steel in 1 M HCl solution, and its inhibition effect was studied with electrochemical experiments, surface analyses, and theoretical calculations. The results revealed that ASP is an effective corrosion inhibitor, and its inhibition efficiency reached up to 94.70% at 800 mg L −1 . Polarization curve experiments indicated that ASP acted as a mixed-type corrosion inhibitor. The adsorption of ASP on the mild steel surface conformed to the Langmuir isotherm model and showed good corrosion inhibition performance in a wide temperature range. The results of surface analyses showed that the corrosion damage of mild steel immersed in HCl solution was significantly reduced with the addition of ASP at 800 mg L −1 . Theoretical studies derived from quantum chemical calculations confirmed the adsorption mechanism of ASP on the steel surface.